Design and Performance Evaluation of a Compact Single-Element LTE/5G Patch Antenna for Vehicular Communication - Abang Madehan, Abang Muhammad Danial; Che Seman, Fauziahanim (Evolution in Electrical and Electronic Engineering, 2026)
This paper presents the design, fabrication and experimental evaluation of a compact single-element microstrip patch antenna intended for LTE and sub-6 GHz 5G vehicular communication. The proposed antenna operates at 2.6 GHz and exhibits a higher-order resonance around 3.5 GHz, enabling dual-band operation without additional slotting or parasitic structures. The antenna geometry was optimised using full-wave electromagnetic simulation to determine the exact performance parameters, including resonant frequency, impedance matching and return loss characteristics. Following optimisation, the antenna was fabricated on an FR4 substrate and experimentally validated using a Vector Network Analyzer (VNA) to measure the reflection coefficient (S11). Measured results show good agreement with simulation, achieving return loss below −10 dB across the targeted LTE band. The results demonstrate that the proposed single-element antenna provides reliable impedance matching and stable performance suitable for vehicular LTE communication.